English as a Medium of Instruction in Community School: Boon or Bane, a Case Study of Nepal - Ramesh Prasad Adhikary (Newinera Publisher, 2020)
The main aim of this research paper is focused on the present debatable issue of Nepalese academia whether the use of English as a medium of instruction in community school is judicious or not. In this research, both the primary and secondary data are used to complete this research. The data are gathered through the questionnaire and interview. For the Primary sources of data twenty-five teachers were selected from the community schools by using purposive sampling procedure. From this study, it is justified that the use of English as a medium of instruction in community schools is beneficial. The use of English helps the progress of the students rather it hampers in their learning activities. The social assumption of Nepalese people that English as medium of instruction as in the private boarding school could make the student excellent has been proved correct. The government should provide all training, courses and infrastructure for the community school for instruction in English medium.